Antioxidant activity of butanolic extract from Madang Gatal (Schima wallichii Choisy) Leaves. Issue 1 (January 2021) - Widiyarti, Galuh; Widodo, Ginanjar; Sampora, Yulianti; Lotulung, Puspa Dewi; Hanafi, Muhammad
Abstract: Antioxidant activity of the butanolic extract from Madang Gatal ( Schima wallichii Choisy) leaves was studied in the research. Antioxidant activity was analyzed using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical oxidation method. Furthermore, the extract was purified using column chromatography to yield 4 partially purified fractions (B1-B4). The extract and B2 fraction possess strong antioxidant action with IC50 value 12.55 and 24.50 μg/ml, respectively. The B1 and B3 fractions have moderate antioxidant activity with IC50 value 70.55 and 90.26 μg/ml, while B4 was not active as antioxidant with IC50 value of 228.28. The target compound of the fraction most active as an antioxidant (B2) was separated by preparative Thin Layer Chromatography (TLC). The isolate was then identified using Fourier Transform Infra-Red (FTIR) and Liquid Chromatography Mass Spectroscopy (LCMS). The IR spectra displayed that the bioactive compound of B2 was predicted as flavonoid with MS 290.25 g/mol. The major compound contained in a putative compound known as catechin with an IC50 value was 17.97 μg/ml.